Habilidades blandas y su incidencia en el clima laboral de los servidores de la empresa pública Aguas del Chuno-EP de Chone - Macías Ganchozo, Luis Mario (2025)
The present research was conducted with the aim of diagnosing the extent to which soft skills impact the work environment of employees at the public company Aguas del Chuno-EP in Chone canton during the 2024 period. The study was descriptive, bibliographic, and field-based, applying inductive, deductive, and analytical-synthetic methods, and was developed in three phases aligned with the specific objectives. In the first phase, a review of the state of the art and the normative framework related to the study variables was conducted, along with an analysis of these variables. The second phase involved the design and application of data collection instruments, including interviews with management and surveys directed at the 88 public employees. The results highlighted various factors negatively affecting the work environment, including deficiencies in effective communication between departments, lack of empathy among colleagues, limited teamwork, absence of recognition for high performance, and inadequate physical conditions for performing job functions. Based on these findings, the third phase involved designing an improvement plan using the 5W+1H matrix, which allowed for proposing strategies aimed at strengthening soft skills and improving the work climate within the evaluated institution. Finally, the results revealed that soft skills play a decisive role in shaping the organizational climate of the employees at Aguas del Chuno-EP in Chone.